E-dinheiro: os bancos comunitários de desenvolvimento rumo à moeda digital? - Santos, Daniel Pereira dos (2024)
This dissertation examines the implementation of the Fintech E-Dinheiro within the context of the solidarity economy, focusing on the Community Development Banks (BCDs) of the Brazilian Network. The main objective is to understand how the E-Dinheiro platform can contribute to the inclusion of BCDs in the national financial system and the alleviation of poverty, discussing the tension between the capitalist model and the solidarity economy. The adopted methodology is a qualitative Case Study, integrating a Systematic Literature Review and Document Research. The specific objectives are: 1. Analyze how E-Dinheiro has contributed to the expansion of financial inclusion and access to quality financial services in impoverished territories where BCDs operate in Brazil. 2. Examine how E-Dinheiro has facilitated the integration of BCDs into the national financial system, broadening their access to financial resources and services. 3. Map and analyze the financial volume of transactions on the E-Dinheiro platform over the past 10 years, identifying key patterns and trends. The results highlight the benefits of the E-Dinheiro platform for BCDs and the national financial system, promoting financial inclusion in marginalized communities with services such as microcredit, transfers, and bill payments. The study concludes that, although E-Dinheiro does not solve all the problems of BCDs and the inclusion of marginalized populations in the national financial system, it is essential for rethinking and implementing a model that ensures effective popular participation, based on the principles of the solidarity economy and popular education. The justification emphasizes the crucial importance of the E-Dinheiro platform for Community Development Banks in Brazil, highlighting its relevance in the context of the increasing digitalization of the economy and the challenges and opportunities at the intersection of the solidarity economy and the capitalist model.